Diagnosis of pulmonary tuberculosis with cartridge based nucleic acid amplification test and light emitting diode fluorescent microscopy: a comparative study - Kumar, Pratik; Bhardwaj, Puneet (International Journal of Advances in Medicine, 2019)
Background: Due to low sensitivity and inability to detect drug resistance, smear microscopy limits its impact on TB control. Culture methods and drug susceptibility testing is complex, time consuming, and takes around 6-8 weeks. A new diagnostic test, cartridge based nucleic acid amplification test (CBNAAT) was developed based on real-time polymerase chain reaction (RT PCR). Objective of this study to compare the results of CBNAAT for diagnosis of pulmonary tuberculosis with LED fluorescent microscopy and sputum culture. Methods: A cross-sectional study was conducted in the department of Chest and TB, CIMS, Bilaspur. Each Sputum sample of presumptive TB patients were tested with CBNAAT, sputum smear microscopy by light emitting diode (LED) fluorescent microscopy (FM) and solid and liquid culture for diagnosis of Tuberculosis. Results of CBNAAT, Fluorescent Microscopy and Culture for detection of Mycobacterium Tuberculosis were compared. Results: The sensitivity and specificity for CBNAAT were 97% and 100% respectively; while that for Fluorescent microscopy were 70% and 100% respectively. The positive and negative predictive value for CBNAAT was 100% and 96% respectively. The positive and negative predictive value for Fluorescent microscopy was 100% and 73% respectively. Conclusion: CBNAAT is having high sensitivity and specificity for diagnosis of pulmonary tuberculosis. It should be routinely used under national health programme to detect a tuberculosis case efficiently.